Study guides

Q: 3a plus 3b-2a plus 5b

Write your answer...

Submit

Related questions

3a+5b+7a=

What is the solution of -2a plus 3a plus 5b

3a + 5b - 6a - 9b = -3a - 4b

Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?

It is an expression that can be simplified to: 3a-2b+c

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

3a - 2b

24am - 9an + 40bm - 15bn = 3a*(8m - 3n) + 5b*(8m - 3n) = (3a + 5b)*(8m - 3n)

It is: 5(3a+b) when factored

15a - 25b + 20 = 5 (3a - 5b + 4)

5(3a - 5b + 4)

ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.

45(3a + 5b)

3a - 2b

a + 7b + 2c

10a+7b undefined variables cannot be determined

5(3a-5b+4)

5b + 5b = 2 x 5b

Area: 15ab Perimeter: 2(3a+5b) or as 6a+10b

(3a - 5b)(9a2 + 15ab + 25b2)

2a+5b isn't possible the answer is still 2a+5b.

15ab square units

The expression is 5b + 16

-b+5b-2b=2b

5b plus 5-3b-7 is 2b-2.